2021
DOI: 10.3390/microorganisms9081568
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium haemolyticum Infection: A Cause of Hemolytic Anemia in a Patient with Bone Marrow Necrosis

Abstract: Clostridium haemolyticum is a sporulating Gram-positive anaerobic rod that is considered to be one of the most fastidious and oxygen-sensitive anaerobes. It is a well-known animal pathogen and the cause of bacillary hemoglobinuria primarily in cattle. To date, human infections caused by C. haemolyticum have been reported in three patients with malignant underlying diseases. We present herein the case of a 30-year-old obese woman with no significant past medical history who developed bacteremia caused by C. hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The pathogenic bacteria that share homology with SARS-CoV-2 are K. pneumoniae, K. grimontii, E. coli, S. Enteritidis, E. faecalis, S. aureus, C. freundii, C. difficile, C. haemolyticum and C. novyi. They can cause infections ranging from common to rare and previous research has demonstrated T cell involvement in combatting the infections (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). They also have the potential to respond via heterologous mechanisms to cross-reactive epitopes and some of these bacteria have been isolated from the lower airways of COVID-19 patients (Table S3).…”
Section: Sars-cov-2 Protein Homology With Pathogenic Bacteriamentioning
confidence: 99%
“…The pathogenic bacteria that share homology with SARS-CoV-2 are K. pneumoniae, K. grimontii, E. coli, S. Enteritidis, E. faecalis, S. aureus, C. freundii, C. difficile, C. haemolyticum and C. novyi. They can cause infections ranging from common to rare and previous research has demonstrated T cell involvement in combatting the infections (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). They also have the potential to respond via heterologous mechanisms to cross-reactive epitopes and some of these bacteria have been isolated from the lower airways of COVID-19 patients (Table S3).…”
Section: Sars-cov-2 Protein Homology With Pathogenic Bacteriamentioning
confidence: 99%